Comparative Sequence Analysis of Multidrug-Resistant IncA/C Plasmids from Salmonella enterica - Hoffmann, Maria; Pettengill, James B.; Gonzalez-Escalona, Narjol; Miller, John; Ayers, Sherry L.; Zhao, Shaohua; Allard, Marc W.; McDermott, Patrick F.; Brown, Eric W.; Monday, Steven R. (Frontiers in Microbiology, 2017)
Determinants of multidrug resistance (MDR) are often encoded on mobile elements, such as plasmids, transposons, and integrons, which have the potential to transfer among foodborne pathogens, as well as to other virulent pathogens, increasing the threats these traits pose to human and veterinary health. Our understanding of MDR among Salmonella has been limited by the lack of closed plasmid genomes for comparisons across resistance phenotypes, due to difficulties in effectively separating the DNA of these high-molecular weight, low-copy-number plasmids from chromosomal DNA. To resolve this problem, we demonstrate an efficient protocol for isolating, sequencing and closing IncA/C plasmids from Salmonella sp. using single molecule real-time sequencing on a Pacific Biosciences (Pacbio) RS II Sequencer. We obtained six Salmonella enterica isolates from poultry, representing six different serovars, each exhibiting the MDR-Ampc resistance profile. Salmonella plasmids were obtained using a modified mini preparation and transformed with Escherichia coli DH10Br. A Qiagen Large-Construct kit™ was used to recover highly concentrated and purified plasmid DNA that was sequenced using PacBio technology. These six closed IncA/C plasmids ranged in size from 104 kb to 191 kb and shared a stable, conserved backbone containing 98 core genes, with only six differences among those core genes. The plasmids encoded a number of antimicrobial resistance genes, including those for quaternary ammonium compounds and mercury. We then compared our six IncA/C plasmid sequences: first with 14 IncA/C plasmids derived from Salmonella enterica available at the National Center for Biotechnology Information (NCBI), and then with an additional 38 IncA/C plasmids derived from different taxa. These comparisons allowed us to build an evolutionary picture of how antimicrobial resistance may be mediated by this common plasmid backbone. Our project provides detailed genetic information about resistance genes in plasmids, advances in plasmid sequencing and phylogenetic analyses, and important insights about how MDR evolution occurs across diverse serotypes from different animal sources, particularly in agricultural settings where antimicrobial drug use practices vary.